A Linguistic Analysis of two Versatile Verbs "qaťa’a" and "šarf" in the Glorious Qur’an with Reference to Their Realizations in English - Abbas, Abdullah Jasim; Ali (Ph.D), Asst. Prof. Hadeel Kamil (South Eastern European Journal of Public Health, 2024)
This study investigates the different morphological patterns, syntactic structures and meanings of the versatile verbs "قطع" and "صرف ". This study analyses these verbs linguistically, providing a holistic view of their usage and versatility within Qur'anic texts. A qualitative approach is used to analyze data. This study aims to investigate the influence of the context on the morphological forms, the syntactic patterns and different meanings of these verbs. Furthermore, it aims to investigate how the translators transfer the linguistic characteristics of these verbs into English. To achieve the aims of the study, the researcher adopts an eclectic model. Accordingly, two verbs are chosen as the study sample. The main findings of this are as follows: firstly, the verb "قطع" is considered versatile due to its meanings only; it has different meanings with fixed syntactic structure (it is transitive in all the selected' Ayahs). The verb "صرف" is considered versatile in accordance with its meanings and syntactic structures; that is, it has different meanings and syntactic structures. Secondly, all the different meanings are considered polysemous senses of the same selected roots. Thirdly, the context is the most influential factor that makes these verbs versatile. Finally, concerning the renderings of the selected Arabic verbs into the TL, it is concluded that sometimes translators have taken the context into account and have rendered some of these verbs into the equivalently TL. Some other times, they do not render these verbs equally.